Finding Jesus in the storm : the spiritual lives of Christians with mental health challenges - Swinton, John, 1957- (Grand Rapids WB. Eerdmans, 2020)
"Practical theology for Christians affected by mental health challenges"--
Includes bibliographical references (pages 219-230) and index.
Keywords: Mental health -- Religious aspects -- Christianity; People with mental disabilities -- Religious life